Pendidikan Jasmani Berbasis Nilai: Membentuk Karakter melalui Aktivitas Fisik pada Siswa - Frans Rivaldo Gulo; Andreas Martin Saputra Waruwu; Rizal Frederick Saragi; Huzaifa Alfatah; Nurkadri (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
Physical education has an important role in shaping students' character through physical activity at school. Through the development of motor skills, physical abilities, knowledge, sportsmanship, as well as mental, emotional, spiritual and social character formation, physical education aims to achieve the goals of the National education system. Apart from that, physical education also has important benefits in improving students' physical fitness and forming characters such as discipline, cooperation and sportsmanship. The difference with sports education lies in the focus on developing motor skills, knowledge and healthy living attitudes through physical activity, while sports education places more emphasis on developing strong athletes and achievements in certain sports. Physical education also includes activities outside the classroom such as field trips, camping, environmental awareness, exploring, and mountain climbing. Values-based physical education combines a character education approach with physical activities to develop students' attitudes, values ​​and social skills. The advantages of value-based physical education include character building, improving mental and emotional health, social skills, and overcoming the problem of accidents at school. Examples of physical activities such as team games, collaborative activities, yoga or meditation classes, and sports competitions can be used as a means to implement values-based physical education.